(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2025)
The research work undertakes an assessment Nigeria leadership role in the Africa union in the Fourth Republic. The study employed the qualitative research method, which allows for data collection using personal observation and interview. The study also reviewed some relevant literature on Africa union and socio economic development. As an analytical tool, the research adopted the National Role theory which highlight that a political behavior always manifest in the performance of a political role. Hence the study further interrogated this role performance in Africa in the 21st Century if there are inherent contradictions that have limited Nigeria’s leadership role performance in Africa. Data were generated from the field which was used to answer the research question. The study found out that over the years Nigeria leaders have tried to live up to the role expectation as per her leadership role in the sub-region. these role play is evident in her numerous peacekeeping mission across the region and other political and economic contributions all geared towards regional stability and to attain this goal, Nigeria have committed its human and material resources for African course. Also as aspect of her leadership role, Nigeria has played a pivotal role in the integration process by strengthening the regional Organization of AU in its operation. However, the great success Nigeria have recorded in her Stabilization and economic integration of the region and sub-region with the kin interest Nigeria pay to her Foreign policy of Africa as the Centerpiece has no direct effect positively on her domestic affairs in terms of development and security. It is established that Nigeria though bedeviled by insurgency and Terrorism here and there still make out time to engage in regional stability without adequately settling of the her domestic affairs. it is expected that a nations foreign policy ought to is a manifestation of her domestic policies but that is not the case in Nigeria rather her foreign policy is executed even at the expense/ detriment of her domestic affairs; this is having a great negative impact on the country and which in turn could affect the leadership role of Nigeria in Africa. Thus the promotion of domestic policies at the national and the regional levels become handy because it will strengthen the leadership role Nigeria plays.